The Concept of Originality and Prior Art in First to Declare: A Strategy to Prevent Unilateral Claims on Traditional Cultural Expressions - Ramadhan, Muhammad Citra (Rechtsvinding, 2025)
The protection of Traditional Cultural Expressions (TREs) within the framework of the modern Intellectual Property Rights system faces significant challenges, primarily due to the dominance of individualistic principles and formal mechanisms based on registration and specifically copyright ownership registration. The first-to-declare system, which initially emphasized recognition of the party who first announced a work or creation, has in practice shifted towards a system that prioritizes formal registration by the first party at the Directorate General of Intellectual Property (DJKI). This article examines the application of the concepts of originality and prior art within the framework of the first-to-declare system, and analyzes their relevance in preventing unilateral claims on TREs by unauthorized parties through the registration mechanism at the DJKI. This research uses a normative juridical approach with an analysis of laws and regulations, international documents, and related case studies. The research results indicate that systemic reforms are needed, including the recognition of collective rights, the development of a TRE database, and the strengthening of the sui generis regime, as preventive measures against TRE misappropriation on the global stage.